Risk Markers for Women's Physical Intimate Partner Violence Victimization in Iran: A Meta-Analysis. (September 2021) - Nikparvar, Fatemeh; Spencer, Chelsea M.; Stith, Sandra M.
In this study, evidence from 14 studies examines 16 unique risk markers for intimate partner violence (IPV) victimization for Iranian women. Large-to-medium effect sizes were found for emotional abuse victimization, depression, poor mental health, poor physical health, partner's drug use, living in a patriarchal household, and partner having experienced child abuse as risk markers. Higher levels of education and higher levels of household income were significant protective markers against IPV victimization for Iranian women. Partner's education, partner's employment, being employed, being pregnant, age, partner's age, and length of the relationship were not significant risk markers for IPV victimization among Iranian women.